Makna Ritus Embob Jengea bagi Kebudayaan Dayak Wehea - Jong , Seratinus; Donatus, Sermada Kelen (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2022)
This study discusses the meaning of the Embob Jengea rite for the Dayak of Wehea culture. The Embob Jengea Rite is one of the traditions in the culture of the Dayak of Wehea which is an expression of gratitude for the harvest, where each person is no longer worried about food shortages because they have received abundant harvests to support their daily needs. This is because agriculture is one of the main livelihoods for the Dayak culture. This research is descriptive and qualitative and utilizes the depth interviews and literature review. This study found that the Embob Jengea rite contains values, such as leadership, gratitude, respect, brotherhood, and art that are relevant to the context of current life. The Embob Jengea Rite is still inherited in the Wehea Dayak culture to this day.